Dental Management of a Child with Dentinogenesis Imperfecta: A Case Report - Najmeh Akhlaghi; Ali-Reza Eshghi; Mehrnaz Mohamadpour (Frontiers in Dentistry, 2016)
Dentinogenesis imperfecta (DI) is a hereditary dentin defect caused by an autosomal dominant mutation in dentin sialophosphoprotein gene. Defective dentin development results in discolored teeth that are prone to wear and fracture. Early diagnosis and proper treatment are necessary to achieve better functional and esthetic results and minimize nutritional deficiencies and psychosocial distress. In order to prevent excessive loss of tooth structure, placement of stainless steel crowns (SSCs) on deciduous and young permanent posterior teeth is recommended as soon as such teeth erupt. This clinical report presents the clinical manifestations and management of a 3.5-year-old child diagnosed with DI type II.